The Effect of Different Angled Abutments with Peripheral Groove and Vent Hole on the Retention of Cement Retained Implant – Supported Restorations - Nuran Yanıkoğlu; Hilal Asutay (Selcuk Dental Journal)
Background: The purpose of this study was to analyze the effect of vent hole or peripheral groove on retention of differently angled (15 ° and 30 o) abutments in of cement retained implant supported restorations. Methods: A total of sixty standart implant abutments were used. Abutments were divided into two groups at 15 ° and 30 ° angles on CNC. According to the modification, each group were divided into 3 subgroups; (1) no modifications, (2) with peripheral groove and (3) with vent hole. Sixty metal frameworks were prepared using laser sintering to fit all abutments. All laser sintered frameworks were cemented with eugenol-free provisional cement. Then, all specimens were thermocycled. The frameworks were removed from the abutments by using the universal test machine and the peak removal force was recorded. Statistical analysis were performed with two-way ANOVA, post hoc Tukey’s (HSD) test-adjusted independent samples t-tests. Results: According to the results, there were significant differences between 15 ° and 30 ° groups in terms of retention values (p < 0.001). Additional hole and grooves enhanced retention in both groups. The highest mean value of vertical pull-out strength (185.00 ± 23.08 N) was showed in 15 ° additional grooves group, and the lowest mean value of vertical pull-out strength (27.60 ± 14.84 N) was showed in 30° control group. Means values of additional groove specimens had the highest scores in both groups. In all groups, there were significant differences between all subgroups (p < 0.05). Conclusion: Increased abutment angle decreases retention, while addition of hole and groove increases.